DEVELOPMENT OF THINKING OF PRESCHOOL CHILDREN IN COGNITIVE AND RESEARCH ACTIVITIES (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the mechanisms and pedagogical conditions that support the development of thinking in preschool children through cognitive and research activities. The preschool age is a crucial period for shaping intellectual curiosity, independence, and the ability to analyze and generalize. The study highlights the role of exploratory learning, sensory experience, and experimental methods in stimulating children’s cognitive development. It also emphasizes the importance of teachers and family in organizing research-based learning environments that encourage creativity and problem-solving. The paper concludes that integrating cognitive and research activities into preschool education fosters flexible, analytical, and creative thinking — the foundation for lifelong learning and intellectual maturity.